Piperacillin/tazobactam versus cefepime or carbapenems for cefoxitin-non-susceptible Enterobacter cloacae, Klebsiella aerogenes, Citrobacter freundii, Serratia marcescens and Morganella morganii bacteraemia in immunocompromised patients. (6th March 2023) - Lu, Brian; Wong, Miranda; Ha, David; Bounthavong, Mark; Banaei, Niaz; Deresinski, Stanley; Diep, Calvin
Abstract: Background: The role of piperacillin/tazobactam for treatment of serious infections due to AmpC-producing organisms remains debatable, particularly in immunocompromised patients. Methods: This was a retrospective cohort study in immunocompromised patients that investigated the effect of definitive treatment with either piperacillin/tazobactam versus cefepime or carbapenems for bacteraemia caused by cefoxitin-non-susceptible Enterobacterales. The primary endpoint was a composite of clinical and microbiological failure. A logistic regression model was constructed to assess the impact of definitive treatment choice on the primary endpoint. Results: A total of 81 immunocompromised patients with blood cultures positive for cefoxitin-non-susceptible Enterobacterales were included for analysis. There was more microbiological failure in the piperacillin/tazobactam arm compared with the cefepime/carbapenem arm (11.4% versus 0.0%, P  = 0.019). Definitive treatment with cefepime or a carbapenem was associated with a decreased odds of clinical or microbiological failure (OR 0.303, 95% CI 0.093–0.991, P  = 0.048) when controlling for baseline characteristics. Conclusions: In immunocompromised patients with bacteraemia due to cefoxitin-non-susceptible Enterobacterales, definitive treatment with piperacillin/tazobactam was associated with an increased risk of microbiological failure and higher odds of clinical or microbiological failure compared with cefepime or carbapenems.